Social cohesion, social participation and HIV testing among men who have sex with men in Swaziland. Issue 6 (2nd June 2016) - Grover, Elise; Grosso, Ashley; Ketende, Sosthenes; Kennedy, Caitlin; Fonner, Virginia; Adams, Darrin; Sithole, Bhekie; Mnisi, Zandile; Maziya, Sibusiso Lulu; Baral, Stefan
ABSTRACT: Social cohesion and social participation are social factors that may help reduce HIV risks and optimize health-seeking behaviors. We examined the association between these factors and HIV testing in the last 12 months among men who have sex with men (MSM) in Swaziland using a cross-sectional survey conducted with 326 men, 18 years of age or older reporting having sex with another man in the last 12 months. Social capital analyses included measures of social cohesion and social participation. The social cohesion measurement scale was created through exploratory factor analysis using polychoric correlations to determine unidimensionality and Cronbach's Alpha to assess internal consistency. The measurement scale was divided at the 25th and 75th percentiles using "high, " "medium" and "low" levels of social cohesion for between-group comparisons. The social participation index included four questions regarding participation, resulting in a participation index ranging from 0 to 4. In the final multivariate logistic regression model, an increase in the level of social participation was found to be significantly associated with HIV testing in the last 12 months, adjusting for age, income, reporting a casual partner, family exclusion and rejection by other MSM due to sexual orientation (adjusted odds ratio [aOR]: 1.3, 95% confidence interval [CI] 1.1–1.7, p  < .01). MSM with high social cohesion had almost twice the odds of HIV testing in the last 12 months (aOR: 1.8, 95% CI 1.1–3.3, p  < .05) as MSM with medium social cohesion, though the overall social cohesion variable was not found to be significant using a Wald test in either the adjusted or unadjusted logistic regression models. These data suggest that building solidarity and trust within and between groups may be a strategy to improve uptake of HIV testing.